2012
DOI: 10.1016/j.cub.2012.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Ability Influences Reproductive Life History Variation in the Wild

Abstract: Cognition has been studied intensively for several decades, but the evolutionary processes that shape individual variation in cognitive traits remain elusive [1-3]. For instance, the strength of selection on a cognitive trait has never been estimated in a natural population, and the possibility that positive links with life history variation [1-5] are mitigated by costs [6] or confounded by ecological factors remains unexplored in the wild. We assessed novel problem-solving performance in 468 wild great tits P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
228
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(234 citation statements)
references
References 39 publications
4
228
1
1
Order By: Relevance
“…There has been a recent surge of interest in individual variation in cognition [49 -51], but the processes that shape this variation often remain unknown. Some studies have shown clear trade-offs between cognitive abilities and fitness [52,53], suggesting that selection can generate variation under different environmental conditions. Our study shows that relationships with personality traits can also generate individual differences in cognitive abilities if these traits affect the probability of infection.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent surge of interest in individual variation in cognition [49 -51], but the processes that shape this variation often remain unknown. Some studies have shown clear trade-offs between cognitive abilities and fitness [52,53], suggesting that selection can generate variation under different environmental conditions. Our study shows that relationships with personality traits can also generate individual differences in cognitive abilities if these traits affect the probability of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there are potential trade-offs between the fitness benefits of enhanced cognitive performance, and costs associated with cognitive traits [44]. In a wild population of great tits (Parus major), parents that were able to solve a cognitive task produced larger clutches than those that failed to solve the task [9]. Task solvers spent less time foraging and foraged over a smaller area than non-solvers, implying that they were more efficient foragers than nonsolvers.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies have implicated a role for male cognitive abilities in the capacity to attract mates, successfully father offspring and efficiently perform parental care, particularly in birds [8][9][10][11][12]. In Drosophila melanogaster, it was shown that male cognitive traits were eroded under relaxed sexual selection, demonstrating a potentially significant role of cognition in the mating system of this species [13].…”
Section: Introductionmentioning
confidence: 99%
“…Less clear is whether the benefits accrued in the long term are any better than strategies adopted by non-innovators, not least because there is no evidence of direct links with robust measures of fitness, such as survival and the total number of offspring recruited by an individual into the breeding population over its lifetime [34]. One study estimated selection on innovative PSP in an iteroparous bird but found no link with the number of offspring recruited to the breeding population (so-called recruitment selection), despite a strong link with fecundity [18]. An antagonistic association between PSP and sensitivity to predators during reproduction was the likely explanation.…”
Section: Introductionmentioning
confidence: 99%